1986
DOI: 10.1002/cm.970060210
|View full text |Cite
|
Sign up to set email alerts
|

Towards a new classification of intracellular particle movements based on quantitative analyses

Abstract: A survey study of organelle movements in a variety of cell types of plant and animal origin was made with the aid of video-enhanced contrast, differential interference contrast (AVEC-DIC) microscopy followed by fine analysis of the motile behavior of the individual organelles. We found that there exists besides Brownian motion a wide spectrum of active motions in cells, i.e. motion that is directionally biased through the expenditure of metabolic energy. The types of active motion seen range from a continuous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

1987
1987
2001
2001

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 27 publications
(32 reference statements)
1
16
1
Order By: Relevance
“…Indeed, when Weiss et al (1986) compared various types of intracellular organelle motility by quantitative motion analysis, they found that "interrupted motion type II" (pauses and direction reversals) is typical for larger organelles, such as lysosomes in cultured cells.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, when Weiss et al (1986) compared various types of intracellular organelle motility by quantitative motion analysis, they found that "interrupted motion type II" (pauses and direction reversals) is typical for larger organelles, such as lysosomes in cultured cells.…”
Section: Discussionmentioning
confidence: 99%
“…Motion analysis of organelle movement along individual microtubules was performed as described using the software packages PARTI-MOVI or SPSS (23,25).…”
Section: Methodsmentioning
confidence: 99%
“…Only occasionally were vesicles observed in close proximity to the cell wall, and these vesicles moved in various directions and with changing velocities in the plane of the plasma membrane as if they were following invisible tracks. Such saltatory movements (interrupted type I according to Weiss et al [1986]) were typical for wounded regions that lacked thick actin filament bundles and/or active unidirectional displacement of organelles. Saltatory movements alternated with trembling or oscillating motions, probably of the Brownian type.…”
Section: Vesicle Dynamics and Organisation Of The Actin Cytoskeletonmentioning
confidence: 99%